Epidemiology of Bacterial Meningitis in the North American Arctic, 2000–2010 - Gounder, Prabhu P.; Zulz, Tammy; Desai, Shalini; Stenz, Flemming; Rudolph, Karen; Tsang, Raymond; Tyrrell, Gregory J.; Bruce, Michael G.
Objective To determine the incidence of meningitis caused by Haemophilus influenzae, Neisseria meningitidis, and Streptococcus pneumoniae in the North American Arctic during 2000–2010. Methods Surveillance data were obtained from the International Circumpolar Surveillance network. We defined a case of bacterial meningitis caused by H. influenzae, N. meningitidis, or S. pneumoniae as a culture-positive isolate obtained from a normally sterile site in a resident with a meningitis diagnosis. Results The annual incidence/100,000 persons for meningitis caused by H. influenzae, N. meningitidis, and S. pneumoniae among all North American Arctic residents was: 0.6, 0.5, and 1.5, respectively; the meningitis incidence among indigenous persons in Alaska and Canada (indigenous status not recorded in Greenland) for those three bacteria was: 2.1, 0.8, and 2.4, respectively. The percentage of pneumococcal isolates belonging to a 7-valent pneumococcal conjugate vaccine serotype declined from 2000–2004 to 2005–2010 (31% to 2%, p-value <0.01). During 2005–2010, serotype a caused 55% of H. influenzae meningitis and serogroup B caused 86% of meningococcal meningitis. Conclusions Compared with all North American Arctic residents, indigenous people suffer disproportionately from bacterial meningitis. Arctic residents could benefit from the development of a H. influenzae serotype a vaccine and implementation of a meningococcal serogroup B vaccine. CC999999/Intramural CDC HHS/United States 2016-08-01T00:00:00Z 25864638 PMC4560175